Waste management practices at Corvinus University of Budapest - Domahidi, Ákos; Baranyai, Dániel (Universitas Diponegoro, 2023)
The best practices of a university waste management considering innovation, impact, and future direction of sustainable universities involve a comprehensive approach that considers not only the environmental impact of waste but also the social and economic dimensions of sustainability. This is especially true for higher education institutions that are meant to educate most future business and social leaders of a country or a region, as is the case at Corvinus University of Budapest. The first step in waste management is to minimize the amount of waste generated. Corvinus achieve this by promoting a culture of sustainability on campus and encouraging students, faculty, and staff to adopt eco-friendly habits, such as using reusable bags, bottles, and containers, and minimizing the use of single-use items and encouraging the use of digital documents instead of paper. After reducing waste generation, the next step is to reuse and recycle as much as possible.Corvinus set up recycling stations that accept a wide range of materials, such as plastics, paper, and electronics. Additionally, Corvinus works with local organizations to donate gently used items, such as furniture and IT, instead of sending them to landfills.Corvinus track their waste generation and disposal to identify areas for improvement and evaluate the effectiveness of their waste management programs. By regularly monitoring and reporting on their waste management practices, Corvinus set goals for improvement and demonstrate their commitment to sustainability.Corvinus collaborate with industry, government, and community groups to find new and innovative solutions for waste management. This include partnering with local waste management organizations to develop sustainable waste management practices, as well as working with local businesses to reduce waste generation. Overall, a successful waste management program at a sustainable university requires a multifaceted approach that incorporates education, outreach, partnerships, technology, and monitoring. By implementing these best practices, universities can reduce their environmental impact, engage students, and staff in sustainable practices, and demonstrate their commitment to creating a more sustainable future.